Processing substandard materials of magnesium-thermal zirconium production - Pylypenko, M.M.; Yanko, T.B.; Stadnik, Yu.S.; Drobyshevska, A.O. (Вопросы атомной науки и техники, 2019)
This paper describes results of study processing of substandard materials and waste of magnesium-thermal production of spongy zirconium to determine the optimal methods of zirconium recycling. The optimal methods of processing that will allow reuse of substandard materials and waste in the process of magnesium-thermal production of sponge zirconium with the content of impurities at the level of world standards are determined.